Assessing the drivers of health-related quality of life among students through regression analysis - Abdul Hadi, Az’lina; Abdul Manaf , Akhtar Fatihah; Mohd Razali, Nornadiah; Azid@Maarof, Nur Niswah Naslina; Azlan, Nuralina (Journal of Islamic, Social, Economics and Development, 2024)
Health-related quality of life (HRQoL) is the term typically used to describe the quality of life that is associated with health and illness. HRQoL is comprised of two main components known as the Physical Component Summary (PCS) and the Mental Component Summary (MCS). This study intends to examine the significant associations between gender, Al-Quran recitation, sunnah practice, social activity, household income, and HRQoL, measured through the PCS and MCS. In addition to the primary objective, this study seeks to determine the significant difference in average PCS and MCS scores between genders. Hence, a cross-sectional study was conducted, involving 386 students who were selected through convenience sampling from a selected university. The Short Form-36 Quality of Life (SF-36) questionnaire was utilized to assess participants’ HRQoL. The data were analyzed using multiple linear regression (MLR). The findings revealed significant effects between gender (p-value<0.001), Al-Quran recitation (p-value < 0.001), sunnah practice (p-value < 0.001), social activity (p-value = 0.003), and household income (p-value < 0.001) on PCS. Likewise, MCS was affected by gender (p-value=0.03), Al-Quran recitation (p-value < 0.001), sunnah practice (p-value < 0.001), social activity (p-value < 0.001), and household income (p-value < 0.001). This indicates that higher levels of Al-Quran recitation and adherence to sunnah practices are associated with a higher HRQoL among students. Moreover, increased engagement in social activities is positively correlated with better HRQoL. Additionally, students with a higher household income tend to have a higher HRQoL, reflecting the importance of financial comfort. Besides, the Independent Sample test reveals that there is a significant difference in the average of both components (PCS, p-value< 0.001; MCS, p-value=0.013). In conclusion, religious practices, social activities, and financial stability have the potential to improve the HRQoL, as well as the mental and physical well-being, of students.